Supporting proactive planning for climate change adaptation and conservation using an attributed road-river structure dataset - Stephanie Januchowski-Hartley (Journal of Environmental Management, 2022)
Freshwater species and their habitats, and transportation networks are at heightened risk from changing climate and are priorities for adaptation, with the sheer abundance and individuality of road-river structures complicating mitigation efforts. We present a new spatial dataset of road-river structures attributed as culverts, bridges, or fords, and use this along with data on gradient and stream order to estimate structure sensitivity and exposure in and out of special areas of conservation (SAC) and built-up areas to determine vulnerability to damage across river catchments in Wales, UK. We then assess hazard of flooding likelihood at the most vulnerable structures to determine those posing high risk of impact on roads and river-obligate species (fishes and mussels) whose persistence depends on aquatic habitat connectivity. Over 5% (624/11,680) of structures are high vulnerability and located where flooding hazard is highest, posing high risk of impact to roads and river-obligate species. We assess reliability of our approach through an on-ground survey in a river catchment supporting an SAC and more than 40% (n = 255) of high-risk structures, and show that of the subset surveyed >50% had obvious physical degradation, streambank erosion, and scouring. Our findings help us to better understand which structures pose high-risk of impact to river-obligate species and humans with increased flooding likelihood.